Dissipative disassembly of colloidal microgel crystals driven by a coupled cyclic reaction network. Issue 6 (30th January 2018) - Go, Dennis; Rommel, Dirk; Liao, Yi; Haraszti, Tamás; Sprakel, Joris; Kuehne, Alexander J. C.
Abstract : We report coupling of a photoacid cycle to a colloidal assembly cycle leading to a dissipative disassembly reaction network. Abstract : A plethora of natural systems rely on the consumption of chemical fuel or input of external energy to control the assembly and disassembly of functional structures on demand. While dissipative assembly has been demonstrated, the control of structural breakdown using a dissipative cycle remains almost unexplored. Here, we propose and realize a dissipative disassembly process using two coupled cyclic reactions, in which protons mediate the interaction between the cycles. We show how an ordered colloidal crystal, can cyclically transform into a disordered state by addition of energy to a chemical cycle, reversibly activating a photoacid. This cycle is coupled to the colloidal assembly cycle via the exchange of protons, which in turn trigger charging of the particles. This system is an experimental realization of a cyclic reaction-assembly network and its principle can be extended to other types of structure formation.